A new macrolactin antibiotic from deep sea-derived bacteria Bacillus subtilis B5. Issue 24 (16th December 2016) - Li, Wei; Tang, Xi-Xiang; Yan, Xia; Wu, Zhen; Yi, Zhi-Wei; Fang, Mei-Juan; Su, Xin; Qiu, Ying-Kun
Abstract: A new macrolactin derivate, 7- O -2′ E -butenoyl macrolactin A (1 ), together with three known macrolactin compounds, macrolactin A (2 ), 7- O -malonyl macrolactin A (3 ) and 7- O -succinyl macrolactin A (4 ), was isolated from the bacterial strain Bacillus subtilis B5, which was isolated from the 3000 m deep sea sediment of the Southwest Pacific Ocean. The structures of the new compounds were assigned by spectroscopic methods including 1-D/2-D NMR and MS analysis techniques. Compounds1 and2 demonstrated antifungal activities against tea pathogenic fungi Pestalotiopsis theae and Colletotrichum gloeosporioides . Abstract :